Gene expression changes in rat brain regions after 7- and 28 days inhalation exposure to exhaust emissions from 1st and 2nd generation biodiesel fuels - The FuelHealth project. (3rd July 2018) - Valand, Renate; Magnusson, Pål; Dziendzikowska, Katarzyna; Gajewska, Malgorzata; Wilczak, Jacek; Oczkowski, Michał; Kamola, Dariusz; Królikowski, Tomasz; Kruszewski, Marcin; Lankoff, Anna; Mruk, Remigiusz; Marcus Eide, Dag; et al.
Abstract: While the impact of emissions from combustion of fossil fuel on human health has been extensively studied, current knowledge of exhaust exposure from combustion of biofuels provides limited and inconsistent information about its neurotoxicity. The objective of the present work was to compare the gene expression patterns in rat frontal cortex and hippocampus after exposure to diesel exhaust emissions (DEE) from combustion of two 1st generation fuels, 7% fatty acid methyl esters (FAME) (B7) and 20% FAME (B20), and a 2nd generation 20% FAME/hydrotreated vegetable oil (SHB20: synthetic hydrocarbon biofuel), with and without diesel particulate filter (DPF). The Fisher 344 rats ( n  = 7/treatment) were exposed to DEE for 7 days (6h/day), and for 28 days (6h/day, 5 days/week) in whole body exposure chambers. The controls were breathing room air. Brain histological examinations did not reveal any adverse exposure-related effects of DEE in frontal cortex or in hippocampus. Gene expression analysis showed that several genes associated with antioxidant defenses and inflammation were statistically differently expressed in DEE exposed animals versus control. In addition, the gene expression changes between the exposure groups were compared, where the observed rank order in frontal cortex was B7 > B20 > SHB20 after 7 days of exposure, and SHB20 > B7 = B20 after 28 days of exposure. In the hippocampus, the rank order was B7 > SHB20 > B20. Effect of DPF treatment was observed for Tnf only. Overall, moderate increases in bio-components in diesel blends do not appear to result in dramatic alterations in gene expression or adverse histopathological effects.